IMPACT OF GENDER DIVERSITY ON TAX COMPLIANCE OF NON-FINANCIAL LISTED COMPANIES IN NIGERIA - Mathias Gboyega OGUNDEJI (Malete Journal of Accounting and Finance)
This study examines the impact of gender diversity on tax compliance of non-financial listed companies in Nigeria. This study employs explanatory sequential design of mixed method to analyse and interpret the quantitative and qualitative data set. 68 out of 116 non-financial listed companies from 2004 to 2018 were selected as the final sample based on data availability while qualitative data was obtained through semi structured interviews on 17 corporate governance agents (Board of Directors; Key Executive Management; Partners of the big four audit companies; Academic Scholars; Regulators; Tax Consultants; and Shareholders). A Generalised Least Squares Regression and Discourse analysis were used to analyse the quantitative and qualitative data respectively. The combined GLS results (Wald Chi squares) indicates that gender diversity (ꞵ=0.0140; P<0.05) has a statistically significant impact on tax compliance. Majority of the respondents subscribed to the idea that having adequate women with knowledge, experience and pedigree will promote the positive tax compliance of listed firms in Nigeria. The study concludes that gender diversity has a significant impact on tax compliance. The study recommends that the FRCN should strengthen the existing code of corporate governance to provide for the appointment of at least, 30% of women of integrity, sufficient knowledge and adequate experience on the board of listed firms in Nigeria in order to achieve tax compliance.